Home

Solve any problem
(step by step solutions)
Input table (Matrix, Statistics)
Mode :
SolutionHelp
Solution
Find f(x)=4x+1, g(x)=2x-3, Find (f+g)(2)

Solution:
Your problem `->` f(x)=4x+1, g(x)=2x-3, Find (f+g)(2)


`f(x)=4x+1`

`g(x)=2x-3`

Now `(f+g)(x)`

`=f(x)+g(x)`

`=``(4x+1)+(2x-3)`

`=4x+1+2x-3`

`=6x-2`

Now find `(f+g)(2)`

`(f+g)(2)``=6*2-2`

`=12-2`

`=10`

`(f+g)(2)=10`






Solution provided by AtoZmath.com
Any wrong solution, solution improvement, feedback then Submit Here
Want to know about AtoZmath.com and me
  
 

Share with your friends
 
Copyright © 2018. All rights reserved. Terms, Privacy